More tales to give you goosebumps : ten spooky stories - Stine, R. L. (New York : Scholastic, 1995)
Contains ten short stories about evil poison ivy, a boy who is turned into a fish, a voice trapped in a seashell, and other creepy happenings.
The werewolf's first night -- P.S. don't write back -- Something fishy -- You gotta believe me! -- Suckers! -- Dr. Horror's house of video -- The cat's tale -- Shell shocker -- Poison ivy -- The spirit of the harvest moon.
"A Parachute Press book"--T.p. verso.
"An apple paperback.".
2.5.
2.5
5-8
Keywords: Horror stories; Short stories; Horror fiction; Short stories